CAUSES OF UNSTABLE HYDRAULIC PROCESSES IN PUMPING STATION PRESSURE PIPES - Ismatova Aziza (Scientific Impulse, 2023)
The strategy is intended to implement the tasks in the priority directions and achieve the main targets and indicators set in the concept of water management development for 2020-2030.